(untitled) (Economic and Political Thought, 2012)
The article presents the analysis of higher education in the United States and proves that the sources of success of the US higher education – in contrast with higher education sectors in other countries – are the freedom of universities to develop their own strategies, competition and relatively high levels of funding. There are obvious lessons to be learned from the American experience but their application requires creativity and sensitivity to local conditions rather than just an attempt to duplicate the American institutions, their policy and funding systems.